Using remote learning to teach clinicians manual wheelchair skills: a cohort study with pre- vs post-training comparisons. (3rd October 2022) - Worobey, Lynn A.; Kirby, R. Lee; Cowan, Rachel E.; Dyson-Hudson, Trevor A.; Shea, Mary; Heinemann, Allen W.; Pedersen, Jessica Presperin; Hibbs, Rachel; Boninger, Michael L.
Abstract: Purpose: To test the hypothesis that remote learning to teach clinicians manual wheelchair skills is efficacious. Materials and methods: A convenience sample of therapists (physical and occupational) and students were enrolled in pairs in a cohort study with pre- versus post-training comparisons. The intervention was a hybrid of self-study and hands-on practice paired with remote feedback for ten intermediate and advanced manual wheelchair skills. Participants practiced with self-selected frequency and duration, uploading a session log and video(s) to an online platform. A remote trainer provided asynchronous feedback prior to the next practice session. Capacity and confidence in completing the ten skills were evaluated using the Wheelchair Skills Test Questionnaire (WST-Q). Knowledge of wheelchair skills training and motor learning was assessed using a 62-item Knowledge Test. Secondary outcome measures included skill achievement, as confirmed by submitted video recordings, and participant feedback about the training. Results: Across 41participants, scores were higher at follow-up compared to baseline for WST-Q capacity (73.9 ± 19.1 vs 16.8 ± 15.6, p < 0.001), WST-Q confidence (80.1 ± 12.2 vs 47.6 ± 18.2, p = 0.003) and knowledge (70.8 ± 7.5 vs 67.0 ± 5.4, p = 0.004). Conclusions: Remote learning can increase wheelchair skills capacity and confidence as well as knowledge about such training and assessment. This model should be further investigated as a delivery method for training rehabilitation professionals. Clinical Trial Registration Number: NCT01807728. Implications for rehabilitation: Wheelchair skills training is one of the 8 steps of wheelchair provision as outlined by the World Health Organization. Wheelchair skills are not a core part of most clinical curriculums and many clinicians cite a lack of resources and uncertainty on how to implement wheelchair skills training into practice as major barriers to providing such training. Remote learning offers the benefits of structured wheelchair skills training with expert feedback on an individual's own schedule that is not afforded by one-day "bootcamp"-type courses or on-the-job training, which are how many clinicians currently learn wheelchair skills. In a sample of physical and occupational therapists and students, remote learning was effective at increasing capacity and confidence to perform manual wheelchair skills as well as knowledge of wheelchair training.